Fixed Point Theorems Under Caristiâ€™s Type Map on Câˆ— -Algebra Valued Fuzzy Soft Metric Space - Srinuvasa Rao, B; N.V.Kishore, G; Vara Prasad, Trkd (International Journal of Engineering and Technology, 2018)
In this paper, we present the extension of Caristiâ€™s fixed point theorems for mappings defined on Câˆ—-algebra-valued Fuzzy soft metric spaces. We establish the existence of simple proof of caristiâ€™s type fixed point theorems in Câˆ—-algebra-valued Fuzzy soft metric spaces and we give some examples which supports our main results.Â Â